(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Article elucidates human impact to of Belarus and specific traits of its synanthropic component. Distribution of species is studied on the base of cell mapping using 390 quadrates (100 km x 100 km). There are 98 apophytic bryophytes in Belarus (53 eventoapophytes and 45 gemiapohytes). Index of synantropization of Belarus bryoflora is 21,2% and it is similar to Ukraine. Some aspects of geography, ecology and distribution of bryoflora on the territory of Belarus and the whole Eastern Europe are discussed. Some centers of apophytic bryoflora are revealed in Eastern Europe.